TINGKAT KECERDASAN SOSIAL SISWA KELAS V SEKECAMATAN ALAK KOTA KUPANG - Treesly Y.N Adoe; Melati Indasari Kale Lena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research discusses the level of intelligence in students, which in essence there are various types, one of which is social intelligence. Social intelligence has an important role in supporting student success in the future. Social intelligence can be developed in the family and school environment. In the school environment, social intelligence can be developed through science learning. The aim of this research is to describe the level of social intelligence of students in class V science and science learning at elementary schools in Alak District, Kupang City. This type of research is quantitative descriptive research with a single variable, namely students' social intelligence. The population in this study were all fifth grade elementary school students in Alak District. The sampling technique used the One Stage Cluster Sampling technique with a sample size of 75 students. Data collection was carried out through questionnaires as the main collection tool and observation as data support. The data analysis technique uses descriptive percentage analysis techniques. The results of this research show that the social intelligence of students in class V science and science learning at SD in Alak District, Kupang City can be seen that 1 student has social intelligence in the very good category, 43 students in the good category and 31 students in the fair category. Overall the level of social intelligence of students with an average score of 57% is in the good category. The conclusion of this research is that the level of social intelligence of students in class V science and science learning at SD in Alak District is in the good category. Suggestions for teachers and schools are to pay more attention to the development of students' social intelligence, both through habituation and integration in science learning.